2020
DOI: 10.1007/s12325-020-01256-7
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Injections in the Treatment of Osteoarthritis Secondary to Primary Inflammatory Rheumatic Diseases: A Systematic Review and Qualitative Synthesis

Abstract: The purpose of this study is to review the current literature on the use of hyaluronic acid (HA) specifically applied to the treatment of osteoarthritis (OA) secondary to primary inflammatory rheumatic diseases. Osteoarthritis should be carefully considered because it has potentially devastating effects on health-related quality of life. Locally injected HA seems to be an effective treatment for OA but it is not clear how to place this treatment in the context of inflammatory rheumatic disorders. To retrieve r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
0
11
0
1
Order By: Relevance
“…Osteoarthritis (OA) is an inflammatory pathology of the diarthrodial joints, characterized by chronic and progressive cartilage degeneration, the formation of osteophytes, subchondral sclerosis, bone hypertrophy and changes in the synovial membrane [11,76,77]. HA is found in the joint, providing viscoelastic properties to the synovial fluid [23,24,78]. The onset of OA, associated with reduced HA synthesis and increased degradation, leads to a shift in distribution towards a lower average MW in the synovium, synovial cavity and cartilage, which consequently decreases the mechanical and viscoelastic properties of the synovial fluid in the affected joint [23,24].…”
Section: Osteoarthritismentioning
confidence: 99%
“…Osteoarthritis (OA) is an inflammatory pathology of the diarthrodial joints, characterized by chronic and progressive cartilage degeneration, the formation of osteophytes, subchondral sclerosis, bone hypertrophy and changes in the synovial membrane [11,76,77]. HA is found in the joint, providing viscoelastic properties to the synovial fluid [23,24,78]. The onset of OA, associated with reduced HA synthesis and increased degradation, leads to a shift in distribution towards a lower average MW in the synovium, synovial cavity and cartilage, which consequently decreases the mechanical and viscoelastic properties of the synovial fluid in the affected joint [23,24].…”
Section: Osteoarthritismentioning
confidence: 99%
“…De Lucia et al in 2020, they reviewed the systematic work comparing the effects of HA and corticosteroids (GKS) in intra-articular injection [23]. A total of 370 HA administrations were evaluated for eight different joints (shoulder, knee, ankle, foot, elbow, wrist, fingers and toes).…”
Section: Review and Disscusionmentioning
confidence: 99%
“…The assessment of treatment effectiveness was performed using various scales of function and pain disorders. In summary, each study resulted in an improvement in joint function and a reduction in pain compared to baseline [23]. Saito et al concluded that, regardless of the joint, both HA and GKS showed similar efficacy in the treatment of rheumatoid arthritis (RA) i OA [24].…”
Section: Review and Disscusionmentioning
confidence: 99%
“…The elasticity and viscosity of synovial fluid are maintained by the HA in normal knee joints. [3][4][5][6] Intra-articular therapeutic modality is preferred over analgesics and non-steroidal anti-inflammatory drugs (NSAIDs) for knee OA management due to significant toxicity and poor tolerability by OA patients with comorbidities. 5 Intra-articular HA is either naturally derived from avian or through bacterial fermentation.…”
Section: Introductionmentioning
confidence: 99%